Pengaruh Budaya Kerja, Produktivitas Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan : Study Kasus PT Natura Lestari Kabupaten Mojokerto - Agus Wiastono,; Indah Datin Nadliroh,; Marlince Kobu Banya, (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
Employee productivity can be high if workers want to improve their abilities so that business objectives can be met effectively and efficiently. The work environment, motivation, and attitude all play a role in high output. The purpose of this research is to identify the impact of the work environment and culture on the output of manufacturing workers at PT Natura Lestari. This study was carried out at PT Natura Lestari with a demographic sample of 90 workers serving as research subjects. The census approach was used in this study's selection. Data was gathered through interviews, recordings, observation, and surveys. Multiple linear regression analysis was used in this research, and it was handled using SPSS version 23 software. According to the findings of the research, the work environment has a favorable and substantial impact on work productivity at PT. Varash Indonesia Jaya. The more pleasant the working atmosphere at PT Natura Lestari, the higher the level of output. At PT Natura Lestari, work culture has a favorable and substantial impact on output. Despite PT Natura Lestari's deteriorating work atmosphere, work output will rise.